Effectiveness of Family-Centered Empowerment Model on Psychological Improvement of Patients With Myocardial Infarction: A Bayesian Multivariate Approach - Mehdi Raei; Mehdi Raei; Mohammad Ghasemi; Kiavash Hushmandi; Nasrin Shirmohammadi-Khoram; Seyedeh Omolbanin Seyedrezaei; Hosein Rostami; Amir Vahedian-Azimi (Frontiers Media S.A., 2022)
ObjectiveThere is a limited understanding of the impact of the family-centered empowerment model (FCEM) on the psychological symptoms in post-myocardial infarction (MI). This study aimed to evaluate the effectiveness of the FCEM on the psychological improvement of patients with MI.MethodsThe present study was a randomized controlled trial (RCT) where patients experienced a standard home cardiac rehabilitation (CR) or CR utilizing the FCEM approach. The empowerment of patients was estimated during nine assessments, such as pre- and post-intervention. Factors, such as quality of life (QoL), state and trait anxiety, and perceived stress, were evaluated. A Bayesian multivariate mixed-effects model was used to simultaneously investigate the effect of the intervention group on study outcomes across the time.ResultsAmong all the participants in this study, 24 (34.3%) were women with a total mean ± standard deviation (SD) of 61.40 ± 12.83 and 24.87 ± 3.80 for age and body mass index (BMI). The participants who were in the FCEM group had a significantly higher mean level of perceived stress (β = 28.80), state anxiety (β = 16.20), trait anxiety (β = 3.65), physical (β = 38.54), and mental QoL (β = 42.14). Moreover, the individuals in the FCEM group had a significantly higher mean level of general health (β = 31.64) in the physical dimension of QoL, vitality (β = 15.04), mental role limitation (β = 21.84), and mental health (β = 18.16) in the mental dimension of QoL.ConclusionsThe FCEM can be a valuable treatment mechanism for patients with post-MI to improve their stress, anxiety, and QoL.